Collaborative Governance in Smart City Makassar: Actors-Networks Across Capacity, Infrastructure, and Policy Domains - Sutanto, Muh. Awalil Resky; Nurmandi, Achmad; Lawelai, Herman; Prakoso, Velandani; Jovita, Hazel; Sohsan, Imron; Agustiyara, Agustiyara (International Journal of Advances in Data and Information Systems, 2026)
This study explores the collaborative governance approach in implementing Smart City Makassar, which faces challenges including low digital literacy, fragmented data, and weak institutional coordination addressing persistent issues of low digital literacy, fragmented data systems, and limited inter-agency coordination that remain underexamined in smart city governance research. Using a qualitative case study method supported by NVivo-assisted network content analysis, data was collected from policy documents, online news, and interviews. The research identifies actor roles, network patterns, and cross-domain integration of policies, infrastructure, and capacities to support smart city sustainability. Findings reveal that digital technologies operate as institutional infrastructures enabling cross-sector interoperability and data-driven coordinationin data-driven decision-making. A tripartite network structure emerges, with government as central orchestrators, private sector as co-innovators driving technological deployment, and citizens as active contributors shaping service responsiveness Matrix-query analysis indicates strong policy–infrastructure integration, highlighting regulation as the structural anchor of collaboration. The success of Smart City Makassar is shaped by the alignment of technical capacity development, regulatory coherence, and adaptive collaborative governance mechanisms. The study positions Makassar as a model for inclusive smart cities in Southeast Asia, contingent upon strengthened public trust and resilient digital infrastructure.